Data Curation Needed to Avoid a Digital Dark Age - Butterfield-Nagy, Desiree (Maine Policy Review, 2015)
An increasingly recognized need for digital curation, or the active selection of digital files and taking steps toward preserving them, has been a natural evolution in an environment where vast amounts of intellectual and cultural content is born digital and may not be represented in tangible form. Desirée Butterfield-Nagy explores the measures that individuals and organizations need to take to ensure we avoid a Digital Dark Age.
Keywords: digital humanities; data curation; data storage systems